2022
DOI: 10.1101/2022.08.24.504952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antimicrobial peptides do not directly contribute to aging inDrosophila, but improve lifespan by preventing dysbiosis

Abstract: Antimicrobial peptides (AMPs) are innate immune effectors first studied for their role in host defense against bacterial and fungal infections. Recent studies have implicated these peptides in the clearance of aberrant cells and various neurological processes including neurodegenerative syndromes. In Drosophila, an array of AMPs are produced downstream of the Toll and Imd NF-κB pathways in response to infection. Many studies have suggested a role for the Imd pathway and AMPs in aging in this insect, supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 116 publications
1
3
0
Order By: Relevance
“…We also describe a clear association between shorter lifespan (95% CI 6 to 28% reduction) and DmelNV infection. This is supported by a recent study showing DmelNV infection in some laboratory stocks can cause greater than 40% lifespan reduction [ 57 ]. However, other reports of the effect of DmelNV on lifespan are mixed [ 26 , 27 , 56 ].…”
Section: Discussionsupporting
confidence: 63%
“…We also describe a clear association between shorter lifespan (95% CI 6 to 28% reduction) and DmelNV infection. This is supported by a recent study showing DmelNV infection in some laboratory stocks can cause greater than 40% lifespan reduction [ 57 ]. However, other reports of the effect of DmelNV on lifespan are mixed [ 26 , 27 , 56 ].…”
Section: Discussionsupporting
confidence: 63%
“…We also describe a clear association between shorter lifespan (95% CI 6 to 28% reduction) and DmelNV infection. This is supported by a recent study showing DmelNV infection in some laboratory stocks can cause >40% lifespan reduction [54]. However, other reports of the effect of DmelNV on lifespan are mixed [25,26,53].…”
Section: Discussionmentioning
confidence: 59%
“…They found that while ablation of individual AMP genes does not impact the animal lifespan during aging, on the other hand, the lack of 14 AMP genes impacts lifespan over aging. Hanson and Lemaitre demonstrate that AMPs control the gut microbiota over aging and protect animal survival, thus demonstrating the importance of gut-microbiota interaction during animal aging ( Hanson and Lemaitre, 2022 ).…”
Section: Model Systems To Study the Dmgb Axis In Neurodegenerative Di...mentioning
confidence: 99%